Interplay Between Optical and Electrical Properties of Nanostructured Surfaces in Crystalline Silicon Solar Cells - Amna Safdar; Yue Wang; Christopher Reardon; Juntao Li; Guilherme S. de Arruda; Augusto Martins; Emiliano R. Martins; Thomas F. Krauss (IEEE Photonics Journal, 2019)
Light trapping has now been recognized as an essential element of highly efficient solar cells. A large number of sophisticated nanostructures have been developed and optically characterized, many of which have been aimed at thin-film silicon technology. It is still an open question whether such nanostructures are beneficial for thick devices, however, especially, since highly efficient solar cells employ >100 μm thick absorber materials and wet etched micron-sized pyramids for light trapping. In this paper, we study and compare the optical and electrical performances of binary quasirandom nanostructures with pyramidal structures to address this question. We show that, while simulations indicate that pyramids have better optical performance, the best overall performance observed experimentally was achieved with binary nanostructures. We found that the experimental short-circuit current for a solar cell patterned with a quasirandom nanostructure is 3.2 mA/cm2 higher than the current observed with pyramids. We attribute this higher current to a better balance between optical performance and surface recombination achieved by the binary nanostructures. This result indicates that binary nanostructures may be beneficial even for thick solar cells.